2010
DOI: 10.1074/jbc.m109.045401
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Orientation of Tricyclic Antidepressants within the Central Substrate Site of the Human Serotonin Transporter

Abstract: The serotonergic system plays an important role in many psychiatric disorders. Its role in depression is well established (1). The majority of antidepressants, including TCAs, 6 cause increased synaptic serotonin (5-HT) levels via blockade of 5-HT reuptake into the presynaptic neuron (2-4) by competitive inhibition of hSERT. TCAs have been in clinical use since the 1950s, with imipramine being the first and most prominent compound (5). In severely depressed hospitalized patients, TCAs appear to be more efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
129
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(144 citation statements)
references
References 42 publications
14
129
1
Order By: Relevance
“…5-HT, the natural substrate of SERT, and amphetamines such as 4-MTA interact with residues Ala96, Asp98 and Phe335 via binding of the protonated amine (Fig. 3A), while the tricyclic antidepressant imipramine is also thought to interact strongly with the Asp98 residue 13,32,37 . A study by Koldsø et al (2010) discovered that the two enantiomers of the SSRI citalopram bind to a central binding site of the hSERT homology model with reversed orientations 38 .…”
Section: Molecular Modellingmentioning
confidence: 99%
“…5-HT, the natural substrate of SERT, and amphetamines such as 4-MTA interact with residues Ala96, Asp98 and Phe335 via binding of the protonated amine (Fig. 3A), while the tricyclic antidepressant imipramine is also thought to interact strongly with the Asp98 residue 13,32,37 . A study by Koldsø et al (2010) discovered that the two enantiomers of the SSRI citalopram bind to a central binding site of the hSERT homology model with reversed orientations 38 .…”
Section: Molecular Modellingmentioning
confidence: 99%
“…S3) (8, 10, 11). Several studies have shown that the equivalent site in monoamine transporters can accommodate inhibitors (17,18,25,26), and mutations of S2 residues in SERT and NET have been found to perturb inhibitor affinity (10,11). To explore whether talopram binds within the S2 site in NET, we introduced 32 single-point mutations into 16 different residues within or in close proximity of the S2 site (Fig.…”
Section: Talopram Is Largely Unaffected By Mutations In the Extracellmentioning
confidence: 99%
“…The structures revealed a topology of 12 transmembrane (TM) spanning regions connected by short intra-and extracellular loops with a high-affinity substrate binding site (denoted the S1 site) centrally located in the core of the transporter protein (12). LeuT has proved to be an excellent structural template for construction of homology models of SERT and NET, facilitating identification of the location and molecular structure of binding pockets for substrates, ions, and inhibitors (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Both models were constructed using the crystal structure of the Aquifex aolicus leucine transporter (LeuT) as a template (Yamashita et al, 2005). The alignment used between LeuT and hSERT and LeuT and hDAT, respectively, was the thoroughly refined one of the neurotransmitter sodium symporters published by Beuming et al (2006) and was previously used by us with success (Celik et al, 2008b;Koldsø et al, 2010Koldsø et al, , 2011Koldsø et al, , 2013aSinning et al, 2010;Severinsen et al, 2012).…”
Section: Molecular Modelingmentioning
confidence: 99%